P317 Assessment of atrial function in elite soccer players. (17th January 2020) - Castro, F A; Lourenco, M; Leite, P V A; Azevedo, O; Dias, G; Faria, B; Nogueira, I; Lourenco, A
Abstract: Introduction: Athlete´s heart is associated with physiological remodelling as a consequence of repetitive cardiac loading. Atrial dilation may occur in athletes, but atrial size is insufficient to provide mechanistic information about the atrium itself and an increase in atrial size is not intrinsically an expression of atrial dysfunction. Two dimensional (2D) LA strain analysis by speckle tracking emerges as a gold standard for evaluation of atrial myocardial function. Aim: To compare LA function between elite soccer players and sedentary healthy controls through 2D-strain analysis by speckle tracking. Methods: We included 44 consecutive male professional soccer players and 25 sedentary male healthy controls, matched by age and race. All subjects underwent transthoracic echocardiogram, including evaluation of LA diameter and volume and 2D-strain analysis by speckle tracking. Peak atrial longitudinal strain (PALS) was measured at the end of the reservoir phase and peak atrial contraction strain (PACS) was measured just before the start of the active atrial contractile phase. The average of PALS and PACS was obtained from the 12 LA segments at apical 4 and 2-chamber views. The LA contraction strain index (CSI) (ratio PACS/PALS x100) was also calculated. SPSS 20.0 was used for statistical analysis. Results: Mean age was similar between athletes and controls (22.3 ± 4.2 vs 25.0 ± 2.4 p = 0.13) as well as body mass index (23.3 ± 5.8 vs 24.6 ± 2.7 Kg/m2, p = 0.24). Athletes had significantly higher LA volume (29.1 ± 6.9 vs. 21.1 ± 5.5, p < 0.001). No statistical differences were observed in LA diameter between the two groups (18.7 ± 2 vs 18.0 ±1.7, p = 0.163). Athletes had significantly lower PALS (36.3%±5.8 vs. 44.2%±8.9, p < 0.001), PACS (9.5%±2.8 vs 15.3%±4.8, p < 0.001) and LA CSI (26.3 ± 7.8 vs. 35.0 ± 9.3, p < 0.001) than controls. LA volume was correlated with PALS (p < 0.001 r = 0.99), but not with PACS or CSI (p = 0.089 and p = 0.142, respectively). Conclusion: This study showed that in top-level athletes LA PALS and PACS are lower and PALS correlates with LA volume, suggesting that LA suffers not only a morphological but also a functional remodelling in response to intensive exercise. This can be mediated by increased LA workload imposed by the increased left ventricular work.